PENGARUH PEMBAGIAN KERJA TERHADAP EFEKTIVITAS KERJA KARYAWAN BAGIAN PRODUKSI PT. TIGA SAUDARA INDONUSA MAKASSAR - Arfiany Arfiany (Fakultas Ekonomi dan Bisnis Universitas Atma Jaya Makassar, 2019)
The concept of managing employees or employees becomes very important in the organization. Seeing the importance of Human Resources (HR) in supporting the progress of an organization must try to get the right workforce both in quality and quantity. Companies are certainly obliged to conduct screening or selection of employees before the division of labor. This is very important and should not be ignored because it can happen that the workforce obtained by the company is not in accordance with the established standards. The selection of the right employee can strengthen an organization in achieving its goals. Mistakenly choosing employees, can be very detrimental in terms of time, cost and morale. In carrying out selection, an organization should determine the requirements that must be met by a prospective workforce before they are rejected or accepted. This aims to make selection as objective as possible. After conducting the selection, the next step that must be done is placement, which is placing the right person in the right position.